Perancangan Sistem Informasi Pembatasan Hak Akses Pengelola Data Pada Aplikasi Core Banking System Temenos T24 - Fitriana, Saghifa; Iskandar, Ardy; Suhada, Satia (Evolusi : Jurnal Sains dan Manajemen, 2024)
The security system is very important in the process of managing data. Security guarantees are needed in information systems, especially in the Core Banking System application. The Core Banking System application used by the author is the Temenos T24 Core Banking System Application. The data manager in the Temenos T24 Core Banking System Application has the role of access rights registered as a Super User. Super User can perform any activity (Full Control) and this activity cannot be known by anyone. This results in all users being able to carry out activities that are not in accordance with their roles and authorities, and there is no recording of activities against users of data management access rights. Therefore, it is necessary to design and develop the Temenos T24 Core Banking System application. The design and development of tools is expected to be able to classify data manager access rights according to roles and authorities, and to be able to record activities on users of data manager access rights. Activity recording is the basis of information from each activity - each role and authority of the user.Keywords: Temenos T24; Core Banking System; Access Rights